Relasi Agama dan Politik di Indonesia - Sonjaya, Adang; Rahayu Diningrat, Budi (CIC Lembaga Riset dan Konsultan Sosial, 2023)
Islamic politics faced challenges in influencing the future of Indonesia during the post-independence era. Modernist Islamic groups struggled to counter the growing influence of the guided democratic authoritarianism regime. As a result, the Islamic political party Masyumi was disbanded, and its leader, Mohammad Natsir, faced derogatory nicknames such as